PENDAMPINGAN PSIKOLOGIS BAGI IBU POSTPARTUM: UPAYA MENGURANGI RISIKO DEPRESI PASCA MELAHIRKAN DI KABUPATEN TUBAN - Ilmiatus Qoyimah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
The mental health of postpartum mothers is an important issue that is often overlooked. Postpartum depression not only affects mothers but also negatively impacts the emotional and cognitive development of babies. In Tuban Regency, awareness and access to mental health services are still limited, with around 10-15% of mothers experiencing postpartum depression. This program aims to provide psychological support for postpartum mothers through several stages: participant identification and recruitment, education, individual counseling, psychosocial support, and health worker training. This program successfully reached 30 postpartum mothers in Tuban Regency. The Evaluation showed a significant increase in mothers' knowledge about postpartum depression and how to manage it. Individual counseling sessions helped mothers to be more open about their feelings and receive the necessary assistance. The psychosocial support groups created a supportive environment for the mothers. The training of local health workers produced workers who could recognize the symptoms of postpartum depression and provide early intervention. The conclusion shows that this psychological support program is effective in reducing the risk of postpartum depression and improving the mental well-being of postpartum mothers. For the sustainability of the program, recommendations include strengthening collaboration, developing comprehensive training modules, conducting regular monitoring and evaluation, and raising awareness about the importance of postpartum mental health. Similar programs are expected to be implemented in other areas to support the mental health of postpartum mothers more broadly.